Learning Outcomes and Inclusive Character Among Elementary Students: A MANOVA Analysis Based on Visual, Auditory, and Kinesthetic Learning Preferences - Restu Syahtini; Yusrizal Yusrizal; Azizah Yusra Amaliyah Harahap; Fatmawati Fatmawati (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Learning outcomes and inclusive character are essential indicators of quality elementary education, yet their relationships across students with different learning preferences remain insufficiently understood. Previous studies have generally examined these variables separately, providing limited evidence within an integrated framework. This study analyzed the relationships between learning outcomes and inclusive character based on visual, auditory, and kinesthetic learning preferences among elementary school students. A quantitative cross-sectional comparative design was employed involving 54 fourth-grade students selected through saturated sampling. Learning outcomes were measured using essay tests, while inclusive character and learning preferences were assessed through questionnaires. PLS-SEM was used exclusively to evaluate instrument validity and reliability, whereas MANOVA examined group differences and hypothesis testing. The multivariate results showed no significant simultaneous effect of learning preferences on learning outcomes and inclusive character (Wilks' Lambda = 0.406–0.712, p > 0.05). However, auditory learning preference demonstrated a significant partial effect on learning outcomes (F = 2.183, p < 0.05), while visual and kinesthetic preferences showed no significant effects. These findings suggest that learning outcomes and inclusive character are influenced more by overall instructional quality than by learning preference classifications alone. The study extends understanding of learning preferences in inclusive elementary education and supports adaptive, student-centered instructional practices.